Nonlinear controller design and testing for chatter suppression in an electric-pneumatic braking system with parametric variation. (1st January 2020) - Wu, Xiuheng; Li, Liang; Wang, Xiangyu; Chen, Xiang; Cheng, Shuo
Highlights: A 2-step control strategy is proposed to deal with the nonlinear chatter leaded by parameter drifting. An adaptive feedforward amplitude-phase regulator is employed to reduce the high frequency oscillation of pressure. A logic rule is designed to ensure that the two controllers work in coordination. Abstract: Accurate pressure control is essential for an electric-pneumatic braking system (EPBS). However, component wear and prolonged service can cause EPBS parameters to drift, which results in system chatter with high frequency. Such is a state of nonlinearity and instability that leads to the gradual deterioration of pressure control. Designing a viable controller for the system is challenging as it requires that system nonlinearity, sensor configuration, and computing capacity be considered. This article addresses the issue and presents a 2-step nonlinear control strategy. An LMS-based adaptive feedforward amplitude-phase regulator is first employed to reduce the frequency of the high frequency pressure oscillation to low frequency's, followed by applying an output feedback controller based on high gain observer to mitigate the low frequency oscillations to realize steady state. A logic rule is designed to ensure that the two controllers work to suppress pressure oscillations of high and low frequencies in coordination. A comprehensive system model is derived to help characterize system nonlinearities and for designing the high gain observer. Numerical and physical validation are executed to demonstrate the feasibility of the strategy and for the performance of the controller design. Experiments results shows that the nonlinear controller can supress the chatter within 0.1 s either in step response or sinusoid tracking when system parameters vary.